KETERSEDIAAN DAN SERAPAN P SERTA HASIL JAGUNG MANIS (Zea mays saccharata Sturt.) DENGAN PEMBERIAN PUPUK UREA DAN PK (11:14) PADA INCEPTISOLS DI JATINANGOR - Sofyan, Emma Trinurani; Sara, Dirga Sapta; Fitriatin, Betty Natalie; Simanjuntak, Edo Kelvin (Jurnal Ilmu-Ilmu Pertanian Indonesia, 2022)
[PHOSPHOROUS AVAILABILITY, ITS UPTAKE AND YIELD OF SWEET CORN UNDER THE APPLICATION OF UREA AND PK FERTILIZERS IN JATINANGOR INCEPTISOLS]. Maize is one of the staple foods cultivated in Indonesia. Low soil fertility causes the low production of maize. Sweet corn requires sufficient nutrients to grow and produce optimally. The application of a combination of Urea fertilizers and PK on sweet corn plants is expected to increase the availability of nutrients and sweet corn crop production. The objective of this study was to determine the effect of Urea fertilizer and PK application on available P, P uptake, and yield of sweet corn (Zea mays saccharata Sturt) on Jatinangor Inceptisols. This research used the Randomized Block Design (RBD) experiment model, consisting of 9 treatments of 1 control treatment (without treatment), 1 standard recommendation of N, P, K fertilizer treatment, and 7 treatments combination of Urea fertilizer and PK. Each treatment was repeated three times. The results revealed that available-P, P uptake, and yield of sweet corn on Jatinangor Inceptisols were affected by the combination of Urea fertilizer and PK. The combination of 300 kg/ha of urea with 215 kg/ha of PK fertilizer increased the available P value until 23,78 ppm, P uptake (0,67 %), and fresh weight of the corncobs (480,27 g plant-1) on Jatinangor Inceptisols.